Diversity and population of thrips species on legumes with special reference to Megalurothrips usitatus - Zafirah Z.,; Azidah A.A., (Penerbit Universiti Kebangsaan Malaysia, 2018)
Thrips (Thysanoptera) are common pests on legume plants, yet little is known about their ecology or diversity in Peninsular Malaysia. In legumes, thrips are typically found in flowers, where their feeding activity causes malformations that eventually lead to crop damage. In this study, we examined the diversity of thrips species, particularly Megalurothrips usitatus, in three selected legume farms around Peninsular Malaysia (Janda Baik, Pahang; Bestari Jaya, Selangor; and Jelebu, Negeri Sembilan). Each month from April 2013 to May 2014, depending on growing season, legume flowers were inspected for thrips in five random plots from each farm. Sampling was performed six times in Bestari Jaya and Jelebu and twelve times in Janda Baik. The most abundant thrips species on legumes was M. usitatus (89.97%) followed by Thrips parvispinus (9.77%), T. hawaiiensis (0.13%) and Ceratothripoides brunneus (0.12%). The abundance of M. usitatus was not different between long bean, French bean and winged bean which equally distributed among different arbitrary strata on legume plants. Temperature and light intensity were found to be positively correlated with the abundance of M. usitatus, but relative humidity showed a negative relationship. M. usitatus was found in large numbers during hot and dry months, but in lower numbers during raining season. This study suggested that wet season may help to regulate the populations of M. usitatus on legume plants.